The Use of Audiovisual Media to Improve Student Understanding in IPAS Lessons - Hardiansyah, Framz; Nurandini , Yuliatin; Zahroh, Finniatus; Amini, Shofiya; Hadi, Kanzil Fikri (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the application of audiovisual media in improving student understanding in Natural and Social Sciences (IPAS) learning at SDN Nambakor 1. The research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with fifth-grade IPAS teachers, classroom observations, and documentation of the learning process. The results show that teachers apply audiovisual media with various strategies, including the use of learning videos, digital presentations through the Canva application, and contextual learning outside the classroom. The application of audiovisual media creates a more engaging learning atmosphere and helps students understand abstract concepts more concretely. Students show high enthusiasm, are more active in asking questions, and are able to relate learning materials to daily life. This research provides an overview of the practice of applying audiovisual media in the IPAS learning in elementary schools.